2020
DOI: 10.3389/fnhum.2020.00213
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Sampling Basis for Visual Processing in Developmental Dyslexia

Abstract: Knowledge of oscillatory entrainment and its fundamental role in cognitive and behavioral processing has increasingly been applied to research in the field of reading and developmental dyslexia. Growing evidence indicates that oscillatory entrainment to theta frequency spoken language in the auditory domain, along with cross-frequency theta-gamma coupling, support phonological processing (i.e., cognitive encoding of linguistic knowledge gathered from speech) which is required for reading. This theory is called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 294 publications
(539 reference statements)
1
37
0
Order By: Relevance
“…The current findings support our previous results, implicating RAP and visual motion processing as the most solid EPs of DD [ 51 ], and provide further support for the role of deficits in the processing of transient and dynamic auditory and visual stimuli in the etiology of DD [ 27 , 28 , 36 , 37 , 42 , 47 , 48 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. These findings further support the dominant, albeit controversial account [ 82 , 83 ], of the M-D theory of DD [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current findings support our previous results, implicating RAP and visual motion processing as the most solid EPs of DD [ 51 ], and provide further support for the role of deficits in the processing of transient and dynamic auditory and visual stimuli in the etiology of DD [ 27 , 28 , 36 , 37 , 42 , 47 , 48 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. These findings further support the dominant, albeit controversial account [ 82 , 83 ], of the M-D theory of DD [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…According to the general M-D theory [ 35 , 47 , 80 , 83 , 84 , 86 ], DD is due to a multimodal sensory impairment in the processing of transient and dynamic stimuli [ 36 , 83 , 85 , 86 ], which might arise from a deficit in neural pathways involved in the fast transmission and processing of sensory information [ 82 , 84 , 89 ]. Successful sequencing depends on the accurate timing of auditory and visual sensory inputs, which leads to hearing accurately the changes in the amplitude and/or frequency of the sounds and to rapidly recognizing and sequencing written letters [ 79 ]. Therefore, accurate timing facilitates the formation of precise memory representations of the order of sounds (phonological processing) and letters in a word (orthographic processing).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The visuospatial processes with relevance to dyslexia involve the magnocellular-dorsal stream (MDS). Multiple studies have found evidence linking dyslexia to the MDS, visuospatial orienting, and the right posterior parietal cortex (e.g., Facoetti et al, 2001 ; Franceschini et al, 2018 ; Fu et al, 2018 ; Vidyasagar, 2019 ; Archer et al, 2020 ). The MDS or “where” stream relays retinal signals, via the lateral geniculate nucleus and along secondary visual pathways, to the right hemisphere dorsal attention network (DAN), which leads in top-down feedback control of visuospatial processing ( Underleider and Mishkin, 1982 ; Grefkes et al, 2010 ).…”
Section: Neural Network Homeostatic Imbalance In Dyslexiamentioning
confidence: 99%